Igennem urenhed til himlen: Den tanato-kosmologiske transformation fra israelitisk religion til kristendom - Jensen, Hans Jørgen Lundager (Religionsvidenskabeligt tidsskrift, 2019)
In the Hebrew Bible, there is no wish for a heavenly existence among human beings; God and his angels on the one hand and human beings on the other, normally maintain a safe distance from each other. Divine beings are potentially deadly for humans, and dead humans are the strongest source of impurity that threatens to encroach upon holy places. With the 'ontological' transformation in antique Judaism and early Christianity that opened up the possibility of an eternal life in heaven, followed a reversal of the value of death-impurity in a manner that resembles Indian Tantrism; no longer something to avoid, the way to heaven passed through dead bodies.